Extreme rainfall analysis and evolution over West Africa during the last 60 years - (:unkn) unknown (My University, 2013)
In West Africa, the sharp decrease of rainfall since the 70s has occurred concurrently with an increase of flood damage. If it is certain that the vulnerability of the population has increased, the question of the evolution of extreme rainfall remains unanswered - especially in a context where global warming should be accompanied by an intensification of the global water cycle. This thesis aims to improve our understanding of the extreme rainfall regime in West Africa. The work is based on three objectives: (i) provide an integrated regional vision of the spatial organization of extremes, (ii) study the evolution of extreme precipitation regime in connection with the decadal variability of annual rainfall (iii) characterize the extreme rainfall by producing rainfall hazard maps and IDAF (Intensity-Duration-Area-Frequency) curves. In this work, two datasets are used: (i) daily data from national networks, available since 1950 on West Africa, have been updated on the Central Sahel until 2010; (ii) precipitation data with high resolution available since 1990 from the AMMA-CATCH Niger observatory. Conventional statistical models from the extreme value theory has been adapted to incorporate covariates in order to represent spatial and temporal non-stationarity in extreme rainfall. These models show a high robustness to estimate the high quantiles and detect regional trends in the extreme series. The theoretical framework of fractals has been used to model the relationships of spatial and temporal scales. Climatological results confirm that the drought of the late 20th century was primarily associated with a decrease in the occurrence of rainfall, intensity remained relatively unchanged. We note, however, a singular behavior in the last decade: a persistent deficit of occurrence of rainfall is compensated by higher intensities which explains a return to better annual rainfall associated with more extreme rainfall.
Keywords: African Research